Efficient gene transduction in pigs and macaques with the engineered AAV vector AAV.GT5 for hemophilia B gene therapy - Yuji Kashiwakura; Kazuhiro Endo; Atsushi Ugajin; Tomohiro Kikuchi; Shuji Hishikawa; Hitoyasu Nakamura; Yuko Katakai; Nemekhbayar Baatartsogt; Takafumi Hiramoto; Morisada Hayakawa; Nobuhiko Kamoshita; Shoji Yamazaki; et al. (Molecular Therapy: Methods & Clinical Development, 2023)
Gene therapy using adeno-associated virus (AAV)-based vectors has become a realistic therapeutic option for hemophilia. We examined the potential of a novel engineered liver-tropic AAV3B-based vector, AAV.GT5, for hemophilia B gene therapy. In vitro transduction with AAV.GT5 in human hepatocytes was more than 100 times higher than with AAV-Spark100, another bioengineered vector used in a clinical trial. However, liver transduction following intravenous injection of these vectors was similar in mice with a humanized liver and in macaques. This discrepancy was due to the low recovery and short half-life of AAV.GT5 in blood, depending on the positive charge of the heparin-binding site in the capsid. Bypassing systemic clearance with the intra-hepatic vascular administration of AAV.GT5, but not AAV-Spark100, enhanced liver transduction in pigs and macaques. AAV.GT5 did not develop neutralizing antibodies (NAbs) in two of four animals, while AAV-Spark100 induced serotype-specific NAbs in all macaques tested (4 of 4). The NAbs produced after AAV-Spark100 administration were relatively serotype specific, and challenge with AAV.GT5 through the hepatic artery successfully boosted liver transduction in one animal previously administered AAV-Spark100. In summary, AAV.GT5 showed different vector kinetics and NAb induction compared with AAV-Spark100, and intra-hepatic vascular administration may minimize the vector dose required and vector dissemination.